Effect of Saturable Absorber Length on Characteristics of Dual Laser Pulses of Passive Q-Switched - Sara A.Shadood; Abdul-Kareem Mahdi Salih; Rasool Asal (مجلة علوم ذي قار, 2024)
The effect of saturable absorber material length on the characteristics of the dual passive Q-switching pulses generated from two wavelengths (  and ) instead of single wavelength was simulated.  Numerical solution of our previous rate equations model using Rung-Kutta-Fahelberg method has been utilized in simulation. Nd+3 :YAG using as an active medium, and Cr+4:YAG as a saturable absorber material. The results showed that  the Nd+3:YAG dual passive Q-switching generated or released at an advanced(earlier) time and characterized by short duration times, high energy and high power with the increasing in the value of . The passive Q-switching for ,  are released respectively at time 58ns, 60 ns approximately at , while released at time 34 ns, 36 ns respectively approximately at . The duration time of   ,  pulses approximate to 16.8ns, 14.6 ns respectively at , while approximate to 10.8 ns ,9.2 ns respectively  at .